Implementation of Consignment in Land Acquisition: Case Study of PLTU Batang - Anggriani, Reni; Rizki Putratama, Galang (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 3 (2022)DO - 10.24843/JMHU.2022.v11.i03.p12, 2022)
Land is the most important means of development because the soil basically does not experience growth or increase in numbers. The development of the times has made the availability of land lower because more and more people need land. On the other hand, the land is necessary to carry out the construction of steam power plants for public use. The problem is how the government can carry out the construction of power plants, especially the construction of the Batang power plant. The purpose of this study is to find out how the implementation of land acquisition for the public interest of pltu in Batang.The research method used is an empirical and normative approach. Land acquisition for the pltu in Batang is carried out by consignment to end the involvement of land acquisition for public use at the Batang power plant. Consignment is carried out in solving problems through stages in order to provide a sense of justice for all parties. this is based on the applicable regulations related to land acquisition for public use.